Green chemistry: synthesis of bioactive heterocycles - Ameta, K. L.; Dandia, Anshu (Springer India Imprint: Springer, 2014)
The book presents a succinct summary of methods for the synthesis and biological activities of various different-sized bioactive heterocycles using different green chemistry synthetic methodologies, like microwave, ultrasonic, water mediated, ionic liquids, etc. The book also provides an insight of how green chemistry techniques are specific to the bioactive heterocyclic compounds.